PREPARATION OF INORGANIC CATALYST BASED HEMATITE (a-Fe2O3) COMPOUND EXTRACTED FROM ACEH IRON ORE MINERAL AND ITS CATALYTIC ACTIVITY ON TRANSESTERIFICATION OF COCONUT OIL - Muliadi Ramli; Anneza Astriet; T. Banta Darmawan; Saiful Saiful; Susilawati Susilawati; Nasrullah Idris (Universitas Syiah Kuala, 2019)
Hematite (Fe2O3) was successfully extracted from the Aceh iron ore mineral by precipitation method with employing sulphuricacid (H2SO4) as chemical agent. Furthermore, the extracted hematite was modified with sodium metal (K), namely it doped with NaOH of 5% and 10% (w/w), respectively. Based on the characterization results using XRD and SEM- EDS proved that modified catalyst (Na2O/Fe2O3) with their homogeneous size were resulted while the hematite (Fe2O3) particles was dopped withNaOH at its low concentration of (5% wt/wt), however while doping with the higher concentration of NaOH (10% w/w), agglomeration was taken place among the catalyst particles in which decreasing the surface area of the modified catalysts. Finally, the modified catalyst (Na2O/Fe2O3) was successfully applied as an inorganic catalyst on transesterification of coconut oil and methanol (T = 55 – 60oC, 2 h)for forming methyl esters asbiodiesel compounds.